Molecular mechanism of ligand bindings to Zika virus at SAM site - Liu, Xiao (2021)
We investigated residue-specific binding free energies using computational alanine scanning with interaction entropy method to identify hot-spots and unravel molecular basis in 3 ligand bindings to Zika SAM binding site. This approach allows one to obtain quantitatively residue-specific contributions to protein-ligand binding free energy. Our computational analysis identified four major residues, W87, I147, H110, and K105 that contribute most to the ZIKV bindings to both SAH and SFG ligands. There are two additional residues, R160 and R163, that also contribute significantly to the binding. Finally, the computed total binding free energies are in good agreement with experimentally measured data.